Corpos reverberantes: novas (re)configurações de fitness e wellness nas academias de ginástica - Rossi, Vanberto José (2014)
This monograph of completion of the course focuses on the social construction of the body in the environment of the gym. The proposal in general terms, is studying it in their everyday social profiles, delineate aspects of its components and establish some relationships between the gym, the subject and society, seeking to understand these relationships, especially with respect to the amount of this establishment to the current historical moment. The gym configures itself as a "no place", a social and a individual link between the parties and all that there is a large confluence of factors in that environment. On the other hand, there are still some traditional characteristics that perpetuate through the gym. Thus, there is the subject that it uses for the cult of the body, moved or not by social imperatives, and also the one who need it to survive, either through clinical or financial imperatives. These types of subject originate social niches that mediate an exchange of interest result of a universe that hovers between the imperatives of social and individual needs.